Improving Learning Interest of Elementary School Students Through Indonesian Language Learning Animation Videos - Amalia, Indah Nur; Khaerunnisa, Khaerunnisa (International Journal of Elementary Education, 2022)
Student learning interest in participating in the learning process will significantly influence learning success. Innovating and updating the teaching and learning process will make the teaching and learning atmosphere more varied, eventually leading to the failure of learning. This study aims to analyze the learning interest of elementary school students by using animated video learning media for Indonesian language subjects in class IV of elementary schools. This type of research is qualitative. The method used in this research is descriptive qualitative. The methods used in collecting data are observation and interviews. The instrument used in collecting data is a questionnaire. The technique used in analyzing the information is descriptive qualitative analysis. The research results show that learning greatly influences students' learning interest in education. The higher the student's interest in education due to new knowledge not obtained by students. Teacher creativity in teaching has a significant role in arousing student interest. It was concluded that the teacher is required to provide innovation in learning so that students can receive learning well. Interesting learning innovations can increase student enthusiasm for learning.